Influence of Pregnant Woman Lacking Chronic Energy Toward Low Birth Weight Events - nurita hardiyanti (NHM PRESS, 2023)
Low Birth Weight (LBW) is defined as birth weight <2500 grams and is a major global health problem. LBW is a contributor to mortality, morbidity and disability in infants and is a major cause of the Infant Mortality Rate (IMR). This problem is closely related to nutritional status. Due to the reduced function of the placenta which delivers nutritional intake from the mother to the fetus. The purpose of this study was to determine the effect of pregnant women with lacking chronic energy on incidence of low birth weight. The type and method of this research is quantitative analytic with cross-sectional research design and using Chi-square analysis. Pregnant women who experienced lacking chronic energy were 29 respondents (64.4%). From 45 respondents there were babies with low birth weight (<2500 grams) as many as 30 respondents (66.7%) and the results of the analysis test using chi-square analysis showed sig. 0.002 < 0.05 which means that there is an influence of pregnant women with lacking chronic energy on the incidence of low birth weight.